Utility of Iron Staining in Identifying the Cause of Renal Allograft Dysfunction in Patients with Sickle Cell Disease - Yingchun Wang; Mona Doshi; Salman Khan; Wei Li; Ping L. Zhang (Case Reports in Transplantation)
Sickle cell nephropathy (SCN) is associated with iron/heme deposition in proximal renal tubules and related acute tubular injury (ATI). Here we report the utility of iron staining in differentiating causes of renal allograft dysfunction in patients with a history of sickle cell disease. Case 1: the patient developed acute allograft dysfunction two years after renal transplant. Her renal biopsy showed ATI, supported by patchy loss of brush border and positive staining of kidney injury molecule-1 in proximal tubular epithelial cells, where diffuse increase in iron staining (2+) was present. This indicated that ATI likely resulted from iron/heme toxicity to proximal tubules. Electron microscope confirmed aggregated sickle RBCs in glomeruli, indicating a recurrent SCN. Case 2: four years after renal transplant, the patient developed acute allograft dysfunction and became positive for serum donor-specific antibody. His renal biopsy revealed thrombotic microangiopathy (TMA) and diffuse positive C4d stain in peritubular capillaries. Iron staining was negative in the renal tubules, implying that TMA was likely associated with acute antibody-mediated rejection (AAMR, type 2) rather than recurrent SCN. These case reports imply that iron staining is an inexpensive but effective method in distinguishing SCN-associated renal injury in allograft kidney from other etiologies.